2019
DOI: 10.1186/s13256-019-2249-7
|View full text |Cite
|
Sign up to set email alerts
|

Adult-onset linear discoid lupus erythematosus on the forehead mimicking en coup de sabre: a case report

Abstract: Background: Linear cutaneous lupus erythematosus (LE) is an unusual form of LE-specific cutaneous condition, occurring in children and young adults. Due to its rarity, the diagnosis of linear cutaneous LE can be difficult and facial lesions can resemble linear morphea or en coup de sabre. Differential diagnosis of similar conditions along the lines of Blaschko must be differentiated from linear LE. Case presentation: We report a case of linear discoid LE on the forehead of an adult female Thai patient mimickin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 16 publications
(25 reference statements)
1
10
0
2
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Dermoscopic features of cutaneous nonscalp DLE lesions (n = 129) were described in 11 studies (three original studies and eight case series/case reports). 6,[21][22][23][24][25][26][27][28][29][30] Two studies reported dermoscopic findings in labial DLE (n = 8), 21,31 one study presented dermoscopy of mucosal DLE (n = 3) 21 and one paper reported dermoscopic features of DLE involving the nail unit (n = 1). 32 The PRISMA flow chart of database search and literature selection is presented in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Dermoscopic features of cutaneous nonscalp DLE lesions (n = 129) were described in 11 studies (three original studies and eight case series/case reports). 6,[21][22][23][24][25][26][27][28][29][30] Two studies reported dermoscopic findings in labial DLE (n = 8), 21,31 one study presented dermoscopy of mucosal DLE (n = 3) 21 and one paper reported dermoscopic features of DLE involving the nail unit (n = 1). 32 The PRISMA flow chart of database search and literature selection is presented in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…[5][6][7][9][10][11][13][14][15][16][18][19][20][21] They were also the most common finding in nonscalp DLE plaques (86/129 lesions; 66.7%). [21][22][23][24][26][27][28][29] Follicular plugs were statistically more common in nonscalp DLE plaques than in scalp lesions (P < 0.001).…”
Section: Follicular Openingsmentioning
confidence: 99%
See 2 more Smart Citations
“…ECDS morphea indicates a peculiar clinical presentation, characterized by an atrophic, indurated area on the paramedian forehead or the frontoparietal scalp, resembling a stroke from a sword. Although very typical, a sim-ilar clinical presentation could be observed in discoid lupus erythematosus, linear lichen sclerosus, and linear alopecia areata [5][6][7][8]. Diagnosis is based on histology; however, specific dermoscopic features have been identified, suggesting a role for noninvasive tool in diagnosis and management of morphea and lichen sclerosus [9].…”
Section: Discussionmentioning
confidence: 99%